Extracorporeal membrane oxygenation in the treatment of critical Pneumocystis jirovecii pneumonia in a child with Langerhans cell histiocytosis: a case report and literature review - Zhuan Zou; Wanlin Zhao; Yulin Chen; Zhongqiang Liu; Guoqian He; Haiyang Zhang (BMC Infectious Diseases)
Abstract Background Children with Langerhans cell histiocytosis (LCH) are particularly susceptible to infections such as Pneumocystis jirovecii pneumonia (PJP) due to the immunosuppressive effects of chemotherapy, which can progress to acute respiratory distress syndrome (ARDS) and respiratory failure. The use of Extracorporeal Membrane Oxygenation (ECMO) to manage hypoxemia secondary to PJP in LCH presents unique challenges, including the prevention of catheter-related bloodstream infections associated with arterial and venous access. This study explores a case wherein ECMO was crucial in treating severe PJP-induced respiratory failure in a pediatric patient with LCH. Case presentation A 3-year-old female with a history of LCH, undergoing long-term chemotherapy and corticosteroid treatment, was admitted with fever, dyspnea, and lethargy. Metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid confirmed Pneumocystis jirovecii (PJ). Despite aggressive management with invasive high-frequency ventilation, inhaled nitric oxide, and prone positioning, the patient’s oxygenation remained critically low, with severe hypercapnia and resultant severe respiratory acidosis, necessitating vasopressor support for hemodynamic stability and venoarterial (VA) ECMO intervention. Early initiation of VA ECMO facilitated ultraprotective lung ventilation and circulatory support, effectively preventing hemodynamic collapse. The patient was successfully decannulated after 13 days of ECMO support. Conclusion While PJP is a rare and extremely serious opportunistic infection, the VA ECMO support in this pediatric case effectively managed severe PJP without ECMO-related complications. This highlights ECMO as a potentially viable, relatively effective, and safe adjunctive therapy in the management of severe PJP infections in children.